REKONSTRUKSI HUKUM KELUARGA ISLAM DALAM PERSPEKTIF MAQASID AL-SYARI’AH UPAYA PREVENTIF PERNIKAHAN DINI DI INDONESIA - Ahmad, Ahmad Fauzi; Taufiq Ikram Ash Syidiqi, Taufiq; Peni Alyanita; Yogi Sopian Haris (USRAH: Jurnal Hukum Keluarga Islam, 2025)
Child marriage remains a prevalent issue in Indonesia, despite the legal minimum age of 19 for both males and females. This practice is not only influenced by economic, cultural, and educational factors but also by misinterpretations of religious teachings that are often used as justification. This study aims to analyze early marriage from the perspective of Islamic family law through the lens of maqasid al-syari’ah as a preventive effort. The research method employed is library research with a qualitative approach by examining Islamic legal literature, statutory regulations, fatwas, and religious court decisions on marriage dispensation, then analyzed using content analysis and critical analysis techniques. The findings reveal that child marriage contradicts the higher objectives of Islamic law, particularly in protecting life (hifz al-nafs), intellect (hifz al-‘aql), and lineage (hifz al-nasl). The dispensation system still creates legal loopholes that weaken child protection. Therefore, reconstructing Islamic family law based on maqasid al-syari’ah is necessary to strengthen child rights protection, postpone marriage until individuals reach physical and psychological maturity, and promote the development of healthy, just, and sustainable families.